Thermal Analysis of ALSI10MG Alloy and Heat Treatment Hardening - ZEKA, Bastri; Muharrem ZABELI; Afrim OSMANI (International Journal of Computational and Experimental Science and Engineering, 2024)
Aluminum which is considered as a metal with use and great perspective belongs to the group of non-ferrous metals due to its low density and suitable physical, mechanical and chemical properties which make its application possible in many branches of modern industry. The mechanical and physical properties of aluminum are significantly improved by its connection with other elements such as; like, Mg, Mn, Cu etc., can be used for the production of various industrial products by molding, lamination, pressing, stamping etc. In this paper the AlSi10Mg alloy was treated, the samples were analyzed by thermal analysis, heat treatment through hardness, the results which showed that the alloy hardness was significantly increased compared to before heat treatment. The purpose of this paper is to look closely at the stages of hardening and the change in hardness after melting and after heat treatment. After the thermal analysis, the stages in detail of their creation in the laboratory conditions used during the experimental work with melting and the solidification process are defined. Experimental work showed that microstructural and mechanical properties changed with heat treatments. It was observed that heat treatment has a great effect to increase hardness of AlSi10Mg. According to Optic Microscope (OM) analysis it can see formation of different phases.